Preparation of Ultracold Li+ Ions by Sympathetic Cooling in a Linear Paul Trap*Supported by the National Basic Research Program of China under Grant No 2010CB832803, the National Natural Science Foundation of China under Grant Nos 11004222 and 91121016, and the Chinese Academy of Sciences. (August 2015) - Chen, Ting; Du, Li-Jun; Song, Hong-Fang; Liu, Pei-Liang; Huang, Yao; Tong, Xin; Guan, Hua; Gao, Ke-Lin
<x content-type="archive" xml:space="preserve">Abstract</x> The 7Li+ ion is one of the most important candidates for verifying QED theory and obtaining the precise value of the fine-structure constant α. However, direct laser cooling of trapped Li+ ions will lead to strong background fluorescence which will influence the spectrum detection. The sympathetic cooling technique is a good choice to solve the problem. In this work, we report sympathetic cooling of 7Li+ ions to few mK using 40Ca+ ions in a linear Paul trap. A mixed ion crystal of 40Ca+ ions and 7Li+ ions are obtained. We also analyze the motion frequency spectra of pure 40Ca+ ions and mixed ions.